GENOME EDITING BERBASIS CRISPR-CAS9 UNTUK MENINGKATKAN TOLERANSI STRES ABIOTIK PADA TANAMAN PADI (ORYZA SATIVA): A SYSTEMATIC LITERATURE REVIEW - Putriwan, Maya; Sumarni; Rachmawaty (Jurnal Biogenerasi, 2026)
Abiotic stresses such as drought, salinity, extreme temperatures, and oxidative stress are major factors limiting the growth and productivity of rice plants. The development of CRISPR-Cas9-based genome editing technology provides a new, more precise approach to modifying genes that play a role in plants' adaptive responses to environmental stresses. This study aims to synthesize the development of genome editing research in rice plants, focusing on the identification of target genes, genome editing strategies, and their impact on increasing abiotic stress tolerance. The method used is a systematic literature review of research articles published in international scientific journals. A total of 31 articles were analyzed in the literature review process, and 22 articles that explicitly reported target genes and genome editing strategies were used in the main synthesis. The results of the analysis showed that most studies targeted regulatory genes that play a role in regulating stress responses, especially groups of transcription factors such as NAC, DREB, bZIP, MYB, and WRKY. In addition, several studies also targeted genes related to ion homeostasis, hormonal signaling pathways, secondary metabolism, and antioxidant systems. The most dominant genome editing strategy was gene knock-out through CRISPR-Cas9-based mutations, while several recent studies have begun to apply multiplex genome editing to target more than one gene simultaneously. Genome-edited rice plants generally show increased tolerance to various abiotic stresses through improved ion homeostasis, increased water use efficiency, cell membrane stability, and strengthened antioxidant systems. These findings indicate that CRISPR-Cas9 is a precision genome engineering approach with the potential to support the development of rice varieties that are more adaptive to environmental changes.